The Effects of Prolonged Treatment with Cemtirestat on Bone Parameters Reflecting Bone Quality in Non-Diabetic and Streptozotocin-Induced Diabetic Rats - Monika Martiniakova; Veronika Kovacova; Vladimira Mondockova; Karol Svik; Piotr Londzin; Joanna Folwarczna; Marta Soltesova Prnova; Milan Stefek; Radoslav Omelka (MDPI AG, 2023)
Cemtirestat, a bifunctional drug acting as an aldose reductase inhibitor with antioxidant ability, is considered a promising candidate for the treatment of diabetic neuropathy. Our study firstly examined the effects of prolonged cemtirestat treatment on bone parameters reflecting bone quality in non-diabetic rats and rats with streptozotocin (STZ)-induced diabetes. Experimental animals were assigned to four groups: non-diabetic rats, non-diabetic rats treated with cemtirestat, diabetic rats, and diabetic rats treated with cemtirestat. Higher levels of plasma glucose, triglycerides, cholesterol, glycated hemoglobin, magnesium, reduced femoral weight and length, bone mineral density and content, parameters characterizing trabecular bone mass and microarchitecture, cortical microarchitecture and geometry, and bone mechanical properties were determined in STZ-induced diabetic versus non-diabetic rats. Treatment with cemtirestat did not affect all aforementioned parameters in non-diabetic animals, suggesting that this drug is safe. In diabetic rats, cemtirestat supplementation reduced plasma triglyceride levels, increased the Haversian canal area and slightly, but insignificantly, improved bone mineral content. Nevertheless, the insufficient effect of cemtirestat treatment on diabetic bone disease does not support its use in the therapy of this complication of type 1 diabetes mellitus.